On the culturally relevant development of Amazonian communities: bio-entrepreneurship, Appropriate technologies, and other alternatives for Good Living - Álvarez Alonso, José (2023)
The persistently high rate of failure in development projects involving local communities in the Peruvian Amazon over recent decades has not prevented the recurrence of these same mistakes year after year, resulting in significant social, environmental, and economic impacts, despite claims of 'sustainability' and 'inclusivity' by many. This paper analyses the factors contributing to this failure, with a particular focus on the lack of understanding of the Amazonian reality and the absence of environmental and cultural relevance in development models imported from other regions. As an alternative approach, we propose the promotion of bio-entrepreneurship initiatives led by families and community interest groups in the Amazonian communities. These initiatives should preferably involve non-timber forest resources, in alignment with the 'forest-oriented' profile of traditional Amazonian societies. Additionally, the application of culturally pertinent technologies and other solutions is recommended.